Epidural dexamethasone showed a better analgesic profile over epidural betamethasone as adjuvant in acute neuropathic lumbar pain - Kitayama, Antonio T; Oliveira, Celia S; Moraes, Natalia V de; Lauretti, Claudia R; Defino, Helton A.; Lauretti, Gabriela R. (International Journal of Advanced Engineering Research and Science, 2022)
Background: The study was designed to evaluate dexamethasone and betamethasone as adjuvants in epidural management of acute radicular pain related to pain, ocular pressure, weight gain and systemic effects. Methods: Twenty six patients with neuropathic pain secondary to disc herniation acted as their own control related to the epidural administration of dexamethasone and betamethasone. Thirteen patients have started with dexamethasone during the first two weekly procedures, and after 3 weeks of wash-out were submitted to two weekly sequences of sacral betamethasone and cross-over. Patients were evaluated related to analgesia, blood pressure, ocular pressure, weight gain, adverse effects and plasmatic measurements of ions, glycemia, ACTH and cortisol. Results: Dexamethasone was superior to betamethasone analgesia (p<0.05). Plasma cortisol and ACTH reduced on the 7th day after the block (p<0.001). The plasmatic concentrations of the ions Na+, K+, Ca++, control and post-prandial glycemia, blood pressure, weight were similar between groups and did no differ from initial control values (p>0.05). Three patients that received dexamethasone after the firs block and 2 that received betamethasone had cortisone glaucoma on day-7 (p<0.001). Discussion: Epidural dexamethasone/lidocaine analgesia was superior to betamethasone/lidocaine analgesia and both drugs resulted in similar unaware increase in ocular pressure and sleep disturbance.